Writing Task : an authentic-task approach to individual writing needs - Jolly, David (Cambridge : New York : Cambridge University Press, 1987)
This student book (accompanied by a teacher text) offers additional practice material and optional exercises on problem aspects of language. It also contains tests which enable students and teachers to assess progress
Keywords: English language -- Textbooks for foreign speakers; English language -- Composition and exercises; English language